PERANCANGAN DAN IMPLEMENTASI JARINGAN RADIUS DI PUSKESMAS BANJIT - Deni; Firmansyah, Firmansyah (LPPM Universitas Bina Sarana Informatika, 2023)
Along with the development of technological advances nowadays, it is very useful for us in looking for information that is fast, precise and accurate in everyday life, especially in helping us complete our work. With the existence of a computerized system, it is hoped that it can help us with all the work that is difficult to do. becomes easy to do in order to get better results than before, Banjit Community Health Center. It requires a lot of overhaul of the network structure that supports and provides satisfactory services for community health center internet users. For this reason, the author wrote this thesis regarding internet network design, currently the Banjit Community Health Center is still using repeaters to spread the internet network throughout the community health center area and using WPA/WPA2 security so that the internet network at several points of the Community Health Center is less stable and feels slow for some users, by using The network design proposed by the author can improve the quality of the internet network at the Banjit Community Health Center.